Corporate Complicity dalam Pelanggaran HAM: Pertanggungjawaban Pidana Korporasi Atas Eksploitasi Buruh Anak di Industri Tekstil (International Forum of Researchers and Lecturers, 2026)
The phenomenon of child labor exploitation in the textile industry is a form of human rights violation that continues to occur in various countries, including in the global supply chains of multinational corporations. This practice not only involves individual perpetrators but also demonstrates the systematic involvement of corporations through production policies, cost pressures, and disregard for labor standards. The concept of corporate complicity is relevant to analyzing the extent to which corporations can be held criminally liable for human rights violations that occur in their business activities. This study aims to examine the forms of corporate involvement in child labor exploitation in the textile industry and analyze the framework for corporate criminal liability from a national and international legal perspective. The research method used is normative legal research with a statutory, conceptual, and case study approach. The results show that corporations can be considered to have participated in or assisted in human rights violations if they know about, allow, or profit from the practice of child labor exploitation. Although various international legal instruments such as the UN Guiding Principles on Business and Human Rights have affirmed corporate responsibility for human rights, their implementation in national law still faces obstacles, particularly regarding proving the element of guilt and imposing criminal sanctions on legal entities. Therefore, strengthening regulations, supply chain oversight mechanisms, and strict law enforcement are needed so that corporate criminal liability can be an effective instrument in preventing the exploitation of child labor and ensuring human rights protection.